Development of Scientific Literacy-Based Student Worksheets (LKPD) for the Classification of Living Organisms Learning Materials - Ali, Sri Herawati; Solikha, Maratus; Paujiah, Epa; Mas’ud, Asrianty; Cahyanto, Tri (FKIP - Universitas Riau, 2025)
Indonesian students’ scientific literacy remains relatively low, as indicated by PISA results, which placed Indonesia among the bottom 10 countries, and AKMI data shows that 51% of madrasah students are at the